If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2/3)*x-((5/3)*x) = 0
(2/3)*x+(-5/3)*x = 0
-1*x = 0 // : -1
x = 0
x = 0
| 4(y+3)=2y+20 | | 3(6)-3(-4)+10(-2)=10 | | 30=5d-3d | | -2.24n=-12.168 | | x-12=x/10 | | 7x-1=8x+2 | | X-3-3x=3(1+x) | | y^4+12y^2+36=0 | | n/-15=5.3 | | 5(2x+6)=55 | | 1.6=4y+20.4 | | 2cos(x)-3x=0 | | 3x+4=9.5 | | n/14.3=-5 | | -0.166666666667= | | 0.5(y+8)=2(y-1) | | 7+8q=7q | | H=-16t^2+24t+40 | | -2x-1=2x+15 | | n/-12.168=-2 | | z+iz+1=0 | | 12(n+8)=132 | | 10(x+3)-9x-4=x-5+3 | | 4x-15=7x-60 | | (7x+15)=8x | | 2(x-4)=35 | | 3/r=12/17 | | y=(7+5k)x | | 4x^2+28x^3=0 | | 3k-5=7k+7 | | 2a+9=22249 | | 4x-31+2x=11 |